Analisis PGA (Peak Ground Acceleration) Berdasarkan Data Gempa untuk Wilayah Jakarta Timur Menggunakan Software PSHA - Siti Ayu Kumala; Didik Nur Huda; Muhamad Candra Irawan (Faktor Exacta, 2018)
The purpose of this research was to produce a contour map of ground motion acceleration (hazard map) for exceeded probability of 10% as an effort to mitigate earthquake tectonics in East Jakarta. This study uses the applied theoretical research method approach using PSHA software. The data used comes from data released from BMKG and the Geological Agency. Based on the map of the acceleration of soil movement (hazard map) in East Jakarta resulting from the PSHA process, for a return period of 500 years (10% PE 50 years) the PGA value generated is 0,03 g - 0, 15 g. East Jakarta is a fairly stable region with a low level of earthquake hazard. Increasingly to the south and southwest, the PGA value is increasing due to close to subduction and volcanic activity. The PGA value in this study is almost the same as the revision of the Indonesian SNI earthquake map 03-1726-02 in 2010.